The development of a porous ceramic water hydrostatic bearing for ultra high precision applications - Almond , R. J. (Cranfield University, 1999)
The principal objective of this research was to produce a series of extremely stiff and thermally stable porous ceramic bearings, and to expand the performance envelope of fluid film technology beyond that currently achievable with conventional oil hydrostatic bearings. The driving force for these developments came from recent advances in ultra- precision and high speed machining, which have placed severe demands on the accuracy and performance of spindle and guide-way bearing systems. A critical part of this research was to develop a material processing methodology, which enabled porous ceramic bearing structures to be manufactured with consistent permeability coefficients. Such control of the material microstructure was necessary in order to produce a useful and predetermined level of performance. The bearings were fabricated using bimodal blends of alumina powder, and vibratory packing into graphite tooling was used to achieve uniform green densities. Following this, the tooling was transferred directly to a hot isostatic press for capsule free high pressure sintering. The influence of temperature and pressure on sintering and permeability was studied, and optimum processing conditions were established. The operation of the water lubricated porous hydrostatic bearing was investigated on a highly instrumented journal test rig. This research has resulted in a bearing with greater stiffness, higher operating speed and lower power consumption than conventional oil hydrostatic technology could achieve. Significant savings were also shown regarding the energy required to drive the spindle assembly, with a reduction in both rotating frictional power and lubricant pumping power consumption.